The Utilization Of Gadgets As A Learning Media During The Covid-19 Students Of The Ibtidaiyah Madrasah Al-Ikhlas Dusun Sidomulyo - Nehrisa Yenda Artisih; Bayu Eko Broto; Abdul Halim (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
During the current pandemic, it is necessary to take extra care of protection for children, whether it is the transmission of Covid-19 or the influence of gadgets, which are very dangerous if you use gadgets too often. There are many impacts that occur in using gadgets for a long period of time, therefore discipline must be applied in using gadgets, if you are used to it then this good thing will be applied wherever this gadget is used, for the sake of eye health and protecting children. The COVID-19 pandemic has had a major impact on various fields, one of which is the education sector. The purpose of this study was to determine the effect of using gadgets in learning during the COVID-19 pandemic as for the relation to student health and student mentality.